Pinus roxburghii Sarg. (Chir Pine): a Valuable Forest Resource of Uttarakhand - Singh, Gopal; Giri, Anand; Paul, Shilpi (Indian Forester, 2017)
Uttarakhand is a hilly state of India and about 71% its area is occupied by different type of forests. Pinus roxburghii Sarg., commonly known as "Chir pine" is one of the most dominant forest plant and it contributes for a huge proportion ( 16.15%) of total forest cover. These pine forests are deeply associated with the livelihood of the people from very ancient time and used it for many purposes. Chir pine is also a common source of several commercially important raw materials like resin, timber, turpentine oil etc., which contributes a remarkable portion in the annual income of this state. Being the part of Indian Western Himalaya, the hills of the state provide best conditions for the growth and propagation of chir pine. Although chir pine has many benefits, it is also responsible for many considerable demerits like forest fire, soil erosion, drought, and water scarcity. Hence, a proper management is necessarily required for better utilization of such a large natural resource available.